The Influence Of Corporate Governance, Financial Performance, And Company Characteristics On Sustainability Report Disclosure - Rohim, Aprillia Fajar; Nugroho, Lucky; Fadjarenie, Agustin (Business, Management & Accounting Journal (BISMA), 2024)
This research aimed to determine the influence of Corporate Governance, Financial Performance, and Company Characteristics on Sustainability report disclosure. This research adopted a quantitative approach and used a panel data regression analysis. Additionally, secondary data was used in this study. It was taken from the Indonesia Stock Exchange, covering the period from 2017 to 2022. A total of nine mining companies were included in the sample size. The results of this study found that the variable (i) the Governance Committee variable had an influence on Sustainability report; (ii) the audit committee variable had an influence on Sustainability report; (iii) the independent board of commissioners variable had an influence on Sustainability report; (iv) profitability did not have an influence on Sustainability report; (v) leverage did not have an influence on Sustainability report; (vi) company size had an influence on Sustainability report. This research is expected to provide information to stakeholders in the mining sector regarding the factors that can influence Sustainability reports. This research is also considered significant as it focuses on the mining sector, which is crucial to Indonesia's economy.